Chemotaxonomic studies on Schwenckia americana LINN - C Wahua; SM Sam (Journal of Applied Sciences and Environmental Management)
This study investigated the chemotaxonomic studies on Schwenckia americana Linn., a member of the family Solanaceae predominantly found mostly in low grass fields, Nigeria. The habit is annual  herbaceous weed with slender stem characterized with free branching and growing up to 45cm in height.They are used mainly as medicine. The leaves are simple, entire, elliptic to ovate in shape, smooth, variable, petiolate and larger at the lower region of stem and narrowing to smaller almost sessile and oblanceolate towards the apical regions which are alternately arranged and acrescently structured from the top to the base up to 3.7 ± 1.5cm long and 2.4±0.6cm wide. The inflorescence is a panicle of 15 or more flowers occurring at stem terminal.The flowers are whitish tubular structures measuring up to 1.0±0.2cm in length and 0.1cm in diameter. The petals are whitish up to 0.9 ±0.2cm in length and sepals are greenish up to 0.1cm in length. The berry fruit is greenish when unripe and  pale yellowish when ripe up to 0.3±0.1cm in diameter. The seeds are blackish and spherical or  triangular shaped with rough edges measuring up to 0.1cm in diameter. The epidermal studies reveal anomocytic stomata whereas the trichomes are simple uniseriate forms wth bulge heads. The anatomy of mid-ribs and petioles showed bicollateral vascular systems. There are three vascular traces and the node is unilacunar. The petioles have 2 rib traces at primary growth phase. At secondary growth phase, the mid-rib and petiole revealed vascular arcs and the stem has a ring of open vascular system. The cytological studies showed a diploid chromosome number of 2n = 24 and n = 12 for the haploids. Alkaloids, saponins, tannins, phlobatannins, flavonoids, combined anthraquinones, free anthraquinones and cardiac glycosides are present.© JASEM